Fine Art Department: Transforming Waste into Art - Tohid, Mohd Suhaimi; Othman, Mohd Fazli; Mohd Zaim, Amirul Aiman; Dzulamarulhilmi, Mohamad Ariff Qarnain; Zainul Idham, Siti Umairah; Mohammad Kinal, Nur Amiera Zam (College of Creative Arts, 2023)
Assoc Prof. Mohd Suhaimi Tohid and Mr. Mohd Fazli Othman led workshop demonstrations. The talented and skillful Fine Arts students helped the demonstrations as a crew. Printed works are produced using discarded materials to be used as a shaped surface or a traditional print concept called Holography. During this workshop, many participants/students from various fields tried and learned the techniques that were carried out. Students from the fine arts department have been trusted to teach and demonstrate together with outside students. The confidence and abilities shown by these students have had a very influential impact on other students regarding the fine arts studied at UiTM.